The Way Cyber Physical Systems Will Revolutionise Maintenance - Jantunen, Erkki (2017)
30th Conference on Condition Monitoring and Diagnostic Engineering Management (COMADEM 2017). 10 to 13, Jul, 2017. Preston, United Kingdom.